2004
DOI: 10.1039/b407622b
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial photodynamic therapy in dermatology

Abstract: Photodynamic therapy (PDT) appears to be endowed with several favourable features for the treatment of localized microbial infections, especially after the advent of cationic photosensitising agents (phenothiazines, meso-substituted porphyrins, polylysine-bound chlorins) which properly interact with the outer wall at the surface of several types of bacterial and yeast cells, increase their permeability, and allow significant amounts of photosensitizer to be accumulated at the level of the cytoplasmic membrane.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
227
1
17

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(249 citation statements)
references
References 134 publications
(104 reference statements)
4
227
1
17
Order By: Relevance
“…They possess a slightly negatively charged surface and are also sensitive to cationic PS, although anionic and neutral PSs can also be used to eradicate Gram-positive bacteria. 5,6,19 The susceptibility differences observed between E. coli and S. aureus and pL-ce6 and TBO may be due to their different chemical properties, as indicated by Demidova and Hamblin et al 12 Although both pL-ce6 and TBO are cationic, pL-ce6 possesses a relatively larger molecular weight and the molecule has a greater number of potentially positively charged groups than TBO. The large molecular weight of pL-ce6 may not facilitate its ready penetration into the cell wall of the Gram-positive S. aureus leading to photodestruction.…”
Section: Discussionmentioning
confidence: 99%
“…They possess a slightly negatively charged surface and are also sensitive to cationic PS, although anionic and neutral PSs can also be used to eradicate Gram-positive bacteria. 5,6,19 The susceptibility differences observed between E. coli and S. aureus and pL-ce6 and TBO may be due to their different chemical properties, as indicated by Demidova and Hamblin et al 12 Although both pL-ce6 and TBO are cationic, pL-ce6 possesses a relatively larger molecular weight and the molecule has a greater number of potentially positively charged groups than TBO. The large molecular weight of pL-ce6 may not facilitate its ready penetration into the cell wall of the Gram-positive S. aureus leading to photodestruction.…”
Section: Discussionmentioning
confidence: 99%
“…33 However, the cationic chlorins appear to be quite effective for such microorganisms. [34][35][36] The PDT inactivation experiments with Candida albicans were also performed to evaluate the effect of these PSs in a fungus cell, as it has a different cell wall when compared to bacteria. 37 We evaluated the PDT activity of both PSs at 20 and 30 μg mL Previous studies have reported the inactivation of Candida albicans with PDT using Photogem, 37 which presents the same complete inhibition with 50 μg mL −1 and a fluence of…”
Section: Photodynamic Inactivation Of Microorganismsmentioning
confidence: 99%
“…Penisilinin 1928'de Alexander Fleming tarafından keşfiyle FDAT eski önemini kaybetmiştir. Ancak, lokalize enfeksiyonlarda sistemik bir tedavinin gerekli olmaması ve antibiyotiklere karşı mikroorganizmaların geliştirmiş olduğu direnç sorunu FDAT'yi yeniden gündeme getirmiştir (30,46,47) . Daha sonraki yıllarda FDAT ile ilgili çalışmalar hız kazanmış ve fotofrin (porfimer sodyum) 1993'te Kanada'da, 1995 yılında ise diğer ülkeler de dahil olmak üzere Amerika'da kullanıma girmiş ve Amerika'da Food and Drug Administration'dan (FDA) klinik kullanım izni almıştır (1,3) .…”
Section: Kısa Tarihçesiunclassified
“…Daha sonraki yıllarda FDAT ile ilgili çalışmalar hız kazanmış ve fotofrin (porfimer sodyum) 1993'te Kanada'da, 1995 yılında ise diğer ülkeler de dahil olmak üzere Amerika'da kullanıma girmiş ve Amerika'da Food and Drug Administration'dan (FDA) klinik kullanım izni almıştır (1,3) . Fotofrinin klinik kullanıma girmesiyle birlikte özellikle son 20 yılda enfeksiyon hastalıklarıyla mücadele-de alternatif bir yaklaşım olarak FDAT ile ilgili çalışmaların sayısında artış olmuş-tur (3,30,38,53) .…”
Section: Kısa Tarihçesiunclassified
See 1 more Smart Citation